Selected plants producing mucilage: Overview, composition, and their potential as functional ingredients in the development of plant-based foods - Lira, Michelle Monteiro; Oliveira Filho, Josemar Gonçalves de [UNESP]; Sousa, Tainara Leal de; Costa, Nair Mota da; Lemes, Ailton Cesar; Fernandes, Sibele Santos; Egea, Mariana Buranelo (Elsevier, 2023)
The increase in the preference for vegan and vegetarian diets is directly related to changing eating habits and the need for plant-based alternatives to animal-based products, which are better for health, due to the high content of essential amino acids and lipid profile rich in polyunsaturated fatty acids, and have lower environmental impacts. In this scenario, there is a growing demand for plant-based foods, making it necessary to find new plant-based ingredients for application in foods and beverages. Flaxseed, chia seed, and Barbados gooseberry contain mucilage, a component with potential application in plant-based products. These hydrocolloids can be used as gelling agents, texture modifiers, stabilizers, and emulsifiers in solid and semi-solid foods. This review presents the extraction, characterization, and application of flaxseed, chia seed, and Barbados gooseberry mucilage for use in plant-based foods. It was found that mucilage composition varies due to the extraction method used, extraction conditions, and geographic location of the seed or leaf. However, applications in plant-based foods are currently limited, mainly focused on applying chia mucilage in bakery products and packaging. Research on applying flaxseed and Barbados gooseberry mucilage to plant-based products is limited, though it has been shown to have potential applications in packaging. Mucilage may also increase the nutritional profile of the product and provide better technological, functional, and sensory characteristics. Therefore, because of mucilage's excellent functional and technological properties, it is a promising candidate to act as an ingredient in plant-based food products.
Keywords: Application; Extraction; Hydrocolloids; Linum usitatissimum; Mucilage; Pereskia aculeata; Salvia hispanica